Strategi Pengelolaan Sampah Rumah Tangga Di Wilayah TPS 3R Tunas Jaya (Studi Kasus Kelurahan Patunas Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat) (Lembaga Pengembangan Kinerja Dosen, 2025)
The TPS 3R Tunas Jaya officially began operations on April 17, 2023, through the Decree of the Head of the Environmental Agency of Tanjung Jabung Barat No. 600.4.15.2/156/LH/2023 and is located in the Patunas sub-district, specifically in RT. 11 and close to residential areas (housing). The issue of waste is one aspect of life that cannot be ignored due to its negative impacts on the environment and public health. The problems at the TPS 3R serving the Patunas sub-district include the lack of community participation in supporting TPS 3R activities and several management issues in managing TPS 3R with many limitations in facilities, human resources, and competencies. This study uses the CIPP evaluation model and will determine further strategies through SWOT analysis.